The Use of Synecdoche in Social Speech Interaction (Journal of the College of Basic Education, 2023)
Synecdoche is a figure of speech in which a part is used to represent the whole and vice versa (Nordquist;2014:1) or it is identified as substituting a more inclusive term for less inclusive one or vice versa such as fireside, hearth-refer to a part of the fire place.The present paper deals with the problem of how to understand the true meaning of synecdoche in the language of the society and how the native speakers use synecdoche in their speech and do they use it just in casual conversation or informal conversation?The paper concludes that people and writers, employ synecdoche in their speech by giving common ideas and objects deeper meanings and thus draw readers' attention. Furthermore , synecdoche is used in different fields of life such as social, political, educational etc..Finally ,Synecdoche ,like any other figure of speech, when it is used appropriately it adds a distinct color to words making them appear vivid .To insert this “life “ factor to literary, political, educational as well as casual conversation. Speakers and writers describe things in new ideas to enable speakers of English language to understand the true meaning of the used words.